The Role of Primary Health Care in Early Detection of Preeclampsia: A Case Series from a Community Health Center - Puri Kahitna Sudibyo (The International Journal of Medical Science and Health Research, 2026)
Introduction: Preeclampsia remains a leading cause of maternal and perinatal morbidity and mortality in Indonesia. Early detection at the primary health care (PHC) level is critical yet often hampered by incomplete risk assessment. This study evaluates the clinical application of the Maternal and Child Health Book (Buku KIA), Poedji Rochjati Score Card (KSPR), Mean Arterial Pressure (MAP), and Roll-Over Test (ROT) for early preeclampsia screening at a community health center. Case Illustration: Three pregnant women at Puskesmas Tambakrejo, Surabaya, are described. Case 1 (38 years, G3P2A0, 20 weeks) had gestational hypertension with a KSPR score of 6 (high-risk), prompting Methyldopa and calcium prophylaxis followed by planned referral. Case 2 (22 years, G1P0A0, 29 weeks) presented with asymptomatic severe preeclampsia (BP 173/121 mmHg, proteinuria 1+, KSPR 12), requiring immediate emergency transfer. Case 3 (28 years, G3P1A1, 4-5 weeks) had chronic hypertension, prior preterm preeclampsia, positive MAP/ROT, and KSPR 12, leading to immediate Amlodipine and tertiary referral. Discussion: Standardized KSPR scoring successfully stratified patients into clear risk categories. MAP and ROT detected subclinical vascular dysfunction, particularly in early gestation. While management aligned with national (POGI) and international (ACOG/WHO) guidelines, gaps persisted in dipstick-only proteinuria assessment, incomplete documentation, and inconsistent prophylactic agent availability. Conclusion: Integrated Maternal and Child Health Book, KSPR, MAP, and ROT screening at the PHC level enables early preeclampsia detection, timely stabilization, and structured referrals. Digitalization, supply chain strengthening, and provider training are recommended to reduce maternal mortality.